A preliminary study of dragonflies diversity at Jeram Tengkek Recreational Forest, Negeri Sembilan / Wan Nurul Nurhidayah Wan Rosly - Wan Rosly, Wan Nurul Nurhidayah (Faculty of Applied Sciences, 2015)
The study of dragonfly at Jeram Tengkek Recreational Forest, Negeri Sembilan.The studies were conducted to determine the diversity and species composition of dragonflies at Jeram Tengkek Recreational Forest, Negeri Sembilan.There were four method used in this study such as a sample collection,killing method, preservation and identification method. A collection of 64 individuals belonging to 13 species fom two families which were Libellulidae and Gomphidae were successfully identified at Jeram Tengkek Recreational Forest, Negeri Sembilan.Libellulidae become the dominant family that recorded at that study site.Orthetrum was the most common genera with 40 individuals. While the least genera were Acisoma and Cratilla with 1 individual respectively. Orthetrum testaceum was found to be the most abundant species recorded at this study site with 25 individuals. The lowest individuals species recorded were Orthetrum triangulare, Orthetrum pruinosum, Orthetrum glaucum, Neurothemis tullia, Acisoma panorpoides and Cratilla metallica with one individual each.Based on the ecological indexes, the value of diversity index (FT) was 2.03, Margalef richness index (R) was 2.89 and Evenness index (E) was 0.80. The ecological indexes showed that Jeram Tengkek Recreational Forest, Negeri Sembilan was diverse and rich with dragonflies.Besides that, the pattern of distribution showed an even distribution.